Kreativitas Anak Desa Sinar Bhakti : Membuat Gelang Manik-Manik untuk Menumbuhkan Jiwa Ekonomi Kreatif - Tiara Listiana; Agus Setiawan; Dinda Fitria; Mayang Sari; Mardiah Kenamon (Jurnal Kabar Masyarakat, 2025)
The creativity of children in rural areas is often overlooked due to limited facilities and opportunities to channel their potential. This community service program aims to empower children in Sinar Bhakti Village through the crafting of beaded bracelets as a form of creative economic activity. The program seeks to enhance fine motor skills, introduce entrepreneurial values, and encourage the development of a creative and productive mindset from an early age. This program employs a participatory method, involving children in hands-on training for crafting beaded bracelets, from material selection to final product assembly. During the training, an educational approach is applied to integrate creative values with economic aspects. The results of this program indicate that the activity successfully improved children’s ability to manage materials and produce marketable products. Additionally, it boosted their self-confidence in showcasing their work, both within the local community and through digital platforms. Another positive impact was the formation of a small creative community focused on developing a local economy based on craft arts. Thus, this program not only provides short-term benefits in terms of technical skills but also long-term advantages by shaping entrepreneurial mindsets.